Comparative Study of Single Flash Steam–ORC and Back Pressure Steam–ORC Configurations in Geothermal Power System - Muaja, Estrela Bellia; Tammy Tinny Veisy Pangow (Jurnal Ilmiah Teknik, 2025)
To support Indonesia’s goal of achieving net-zero emissions by 2060, optimizing the utilization of renewable energy sources is essential. In geothermal systems, brine—commonly considered waste—can be further harnessed to maximize resource efficiency and sustainability. The Organic Rankine Cycle (ORC) presents a promising technology to significantly increase the power output and efficiency of geothermal power plants. This study aims to evaluate the turbine power output of two power generation system configurations integrated with ORC technology, using three different working fluids: Iso-pentane, R-290, and R-1234. The research method involves the development of mathematical and thermodynamic models to simulate and analyze energy conversion processes and calculate turbine power output in each configuration. The results show that the back pressure steam–ORC configuration generates substantially higher total power than the single flash steam–ORC system. Specifically, the back pressure system achieves 33.53 MW with Iso-pentane, 39.3 MW with R-290, and 47.6 MW with R-1234. The performance improvement is most significant when using R-1234, with a 19 MW increase compared to the single flash configuration. Meanwhile, the increase is only 1.46 MW for Iso-pentane and 0.8 MW for R-290. These findings highlight the superior efficiency of the back pressure steam–ORC configuration, particularly when paired with R-1234, as a promising solution for enhancing geothermal energy utilization in Indonesia.